2019
DOI: 10.1186/s40425-019-0695-9
|View full text |Cite
|
Sign up to set email alerts
|

Late-differentiated effector neoantigen-specific CD8+ T cells are enriched in peripheral blood of non-small cell lung carcinoma patients responding to atezolizumab treatment

Abstract: BackgroundThere is strong evidence that immunotherapy-mediated tumor rejection can be driven by tumor-specific CD8+ T cells reinvigorated to recognize neoantigens derived from tumor somatic mutations. Thus, the frequencies or characteristics of tumor-reactive, mutation-specific CD8+ T cells could be used as biomarkers of an anti-tumor response. However, such neoantigen-specific T cells are difficult to reliably identify due to their low frequency in peripheral blood and wide range of potential epitope specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 43 publications
(62 reference statements)
4
51
0
Order By: Relevance
“…Hundreds of candidate epitopes spanning the complete SARS-CoV-2 genome were recently identified as potential targets for a CD8+ T cell response to SARS-CoV-2 14 , 15 . A triple-coded multiplexed peptide-MHC tetramer staining approach was used to screen 408 potential epitopes for recognition by T cell responses across 6 different HLA alleles: HLA-A*01:01, HLA-A*02:01, HLA-A03:01, HLA-A*11:01, HLA-A*24:02 and HLA-B*07:02 16 , 17 . In addition, CD8+ T cells were probed for reactivity against up to 20 different SARS-CoV-2-unrelated control peptides per HLA for each sample (CMV-, EBV-, Influenza-, Adenovirus-, and MART-1-derived epitopes; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundreds of candidate epitopes spanning the complete SARS-CoV-2 genome were recently identified as potential targets for a CD8+ T cell response to SARS-CoV-2 14 , 15 . A triple-coded multiplexed peptide-MHC tetramer staining approach was used to screen 408 potential epitopes for recognition by T cell responses across 6 different HLA alleles: HLA-A*01:01, HLA-A*02:01, HLA-A03:01, HLA-A*11:01, HLA-A*24:02 and HLA-B*07:02 16 , 17 . In addition, CD8+ T cells were probed for reactivity against up to 20 different SARS-CoV-2-unrelated control peptides per HLA for each sample (CMV-, EBV-, Influenza-, Adenovirus-, and MART-1-derived epitopes; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antigen-specific triple tetramer positive cells (hits) were identified by an automated peptide-MHC gating method 17 and each hit was confirmed and refined using manual gating. The designation of bona fide antigen-specific T cells was further dependent on (i) the detection cut-off threshold (≥2 events to be detected in each staining configuration), (ii) the frequency correspondence between the two tetramer staining configurations ( ratio between the frequencies of a hit in either staining configuration to be ≤2) and (iii) the background noise (frequencies of specific CD8 T+ cell events must be greater than events from the corresponding CD4 T cell population), as unbiased objective criteria for antigen-specificity assessment 16 . Bulk T cells and true hits from both staining configurations were combined for assessing frequencies, phenotypic and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies had shown that memory T cells from peripheral blood could respond to neoantigens in tumor tissue (38), and CD8 + PD-1 +/high T-cell subsets were preferentially enriched upon neoantigen stimulation (39,40). Analyzing features of CD8 + T cells seemed to be an alternative choice for monitoring immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Neoantigen-specific T cells can be identified in patients not only with melanoma, but also with epithelial cancers, such as lung cancer [119,120], gastrointestinal cancer [121][122][123], ovarian cancer [124][125][126], breast cancer [127] and pancreatic cancer [128]. Case reports have demonstrated that treatment of the gastrointestinal and breast cancer patients with a T cell population highly enriched in neoepitope-specific T cells caused tumour regression [121,123,127].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%